Predigt und Politik im frühmittelalterlichen Bayern Arn von Salzburg, Karl der Große und die Salzburger Sermones-Sammlung - Diesenberger, Maximilian (Millennium-Studien / Millennium Studies, 2015)
Many sermon manuscripts were created around 800 CE over the course of the Carolingian reform movement, but until now, historical researchers have largely overlooked them. The presentation analyzes selected sermon collections to reveal their importance as a medium for implementing reforms at the local level, thereby making them an important instrument of Carolingian rule.